Sexually transmitted infections in oral cavity lesions: Human papillomavirus, Chlamydia trachomatis, and Herpes simplex virus - Mosmann, Jessica P. (J Oral Microbiol, 2019)
Objective: Provide evidence of HPV, C. trachomatis, and HSV infection in the oral cavity from patients with different types of stomatological lesions. Materials and Methods: Oral swabs samples were collected from a total of 318 patients. The infectious agents were analyzed using the PCR technique. HPV genotyping and HSV type were studied using the RFLP method. Results: We studied 137 benign lesions (B), 96 potentially malignant disorders (PMD) and 85 oral squamous cell carcinomas (OSCC). The prevalence of HPV was 34%. The most frequently genotypes detected were 6 low risk and 16 high risk. The prevalence of C. trachomatis was 16% and HSV 3%. Co-infections were detected mostly in benign lesions as following: HPV-C. trachomatis in 4%, C. trachomatis- HSV in 1.8% and HPV-HSV in 0.3%. Conclusion: This report is the first contribution to the identification and genotype characterization of HPV in a scenario little studied in our area, and it also contributes to improving our understanding on sexually transmitted infectious agents and their associations with the oral cavity. Besides, we detect the presence of C. trachomatis and HSV and co-infection with HPV in the oral cavity, which they should be taken into account for diagnostic and treatment purposes.